Evaluation of Cowpea (Vigna unguiculata L) Mutant Genotypes under Hydroponic Conditions Using Different Levels of Phosphorus Concentration - (:unkn) unknown (My University, 2025)
Cowpea yields in the sub-Sahara African region are low primarily due to low available soil health, poor varieties and farming management. The present study aims to assess the performance of mutant genotypes of cowpea (Vigna unguiculata L) under hydroponic conditions, specifically focusing on different levels of phosphorus concentration. This study was conducted at the University of Zambia, School of Agricultural Sciences, plant physiology laboratory. The experiment was set up as a 5 x 8 factorial completely randomized design replicated three times with varying P amounts of 0mg/L, 4mg/L, 8mg/L, 12mg/L, and 16mg/L in a nutrient media and eight genotypes, giving a total of 120 experimental units assigned randomly to each plot (black plastic container). Genotypes showed significant differences (p<0.001) in response to all measured parameters (shoot length, root length, lateral roots, shoot biomass, and root biomass) across phosphorus concentrations. Similarly, the responses of all measured parameters in different P concentrations across genotypes were significantly different (P < 0.001). The current study identified the mutant line LT-3-8-4-1 as a better performer in the variables under consideration across different P-concentrations. However, mutant lines LT-3-8-4-1, LT-11-5-1-1, and LT-4-2-4-1 were identified as the best performers in the P-limiting solution (with P amount at 4mg/L). Furthermore, mutant line LT-3-8-4-1 exhibited a better adaptive flexibility performance than the parent (Lutembwe) in media with a P concentration ranging from 0 to 16 mg/L while the three genotypes, LT-3-8-4-1, LT-11-5-1-1, and LT-4-2-4-1 were considered as genotypes of choice in areas where there are p-limiting soils. In addition, the phenotypic variation explained showed that only 9.79% of the change in shoot length is explained by the change in root length. This implies that shoot length can only be used to estimate the root length in selecting for
Keywords: African Research